1993
DOI: 10.1021/j100144a023
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of diborane and ammonia gas mixtures in a chemical vapor deposition hot-wall reactor

Abstract: Boron nitride has been deposited'by chemical vapor deposition from diborane and ammonia gas mixtures, in the form of either films or powders depending on the pressure in the reactor. IR analysis of the boron nitride deposits has been used to obtain the composition of the films. In the temperature range studied, 600-850 OC, the effect of the deposition temperature on the reaction kinetics has been interpreted by assuming a change in the relative concentration of activated species arising from diborane and ammon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

1994
1994
2006
2006

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 5 publications
1
15
0
Order By: Relevance
“…We have studied the effect of diborane flow rate on the composition, structure, and stability of CVD boron nitride films deposited at 800 °C and 267 Pa from ammonia and diborane gas mixtures, keeping the ammonia flow rate constant at 100 sccm. This work confirms our previous view that the reaction mechanisms for the formation of the boron nitride films for a given deposition temperature are controlled by the relative composition of the gas mixture . For low [B 2 H 6 ]/[NH 3 ] ratios, turbostratic boron nitride films were preferentially obtained at low deposition rates (≈40 nm/min), whereas amorphous films were formed at high deposition rates (≈160 nm/min) when high [B 2 H 6 ]/[NH 3 ] ratios are used.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…We have studied the effect of diborane flow rate on the composition, structure, and stability of CVD boron nitride films deposited at 800 °C and 267 Pa from ammonia and diborane gas mixtures, keeping the ammonia flow rate constant at 100 sccm. This work confirms our previous view that the reaction mechanisms for the formation of the boron nitride films for a given deposition temperature are controlled by the relative composition of the gas mixture . For low [B 2 H 6 ]/[NH 3 ] ratios, turbostratic boron nitride films were preferentially obtained at low deposition rates (≈40 nm/min), whereas amorphous films were formed at high deposition rates (≈160 nm/min) when high [B 2 H 6 ]/[NH 3 ] ratios are used.…”
Section: Discussionsupporting
confidence: 88%
“…Two regions, with low ( r ≤ 0.25) and high deposition rates ( r > 0.25), can be distinguished in the curve, and these can be associated with two different growth mechanisms for the boron nitride films. In a previous work concerning the temperature effect on the boron nitride deposition (600−850 °C range) we considered borazine and aminodiborane as the two most probable intermediates for the BN synthesis . In the temperature range of the study and for a [B 2 H 6 ]/[NH 3 ] ratio of 0.056, we concluded that an increase in the temperature produces a change from aminodiborane to borazine as an intermediate compound.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Note that at low temperature, the most thermodynamically favorable product in the gas phase reaction is the needle-shaped cluster with n=16, which dominates the gas phase up to 800-900 K. As the temperature was increased further, low-mass clusters became more pronounced due to the entropy factors. The trimeric imido compound was predicted to be the most stable gas phase molecule at temperature higher than 1100 K. It was supported by available experimental evidence, 25 from which (HBNH) 3 has been obtained as the intermediate compound at 775 ℃. In addition, the octamer has considerable abundance at higher temperature.…”
Section: Energetics Of the Oligomerization Reactionsmentioning
confidence: 62%